Exclusive Breast Milk Education with Android-Based Application Program Towards Breastfeeding Patterns - Wahyuni, Sri; Djamiloes, Fauzia; Mulyati, Sri; Budhi, Ni Gusti Made Ayu Agung (jitek, 2023)
During the Covid-19 pandemic, education, which so far has been carried out directly, has switched to education through various online media, but the effectiveness of education through these applications needs to be evaluated. The aim of the study was to increase pregnant women's knowledge about exclusive breastfeeding and to find out the effect of android-based application programs on breastfeeding patterns. The research design was quasi-experimental with a pre and post-test control group design, subjects were grouped into intervention groups and control groups, selected by purposive sampling with a total of 30 people in each group. This research was conducted in 2022 in the Sindang Barang and Cipaku Health Centers, Bogor City. The independent variable is the Android-based ASI application program with the dependent variable being the pattern of breastfeeding. The statistical test uses the Wilcoxon and Mann Whitney tests. The results of the study showed that there was a significant increase in the average knowledge and attitude after exclusive breastfeeding education was carried out with Android-based application program, as well as a significant change in the pattern of breastfeeding after participating in the breastfeeding education program. The conclusion of the study is that there is a significant relationship between breastfeeding education and Android-based application program on increasing knowledge, attitudes of mothers and patterns of breastfeeding.